Estudio comparativo entre los proyectos internet satelital Starlink y Kuiper. - Rodríguez Pisco, Roberto José (2022)
The present comparative study was carried out with the purpose of making known, through theoretical research, the characteristics of the Starlink and Kuiper satellite internet projects. Currently in the telecommunications market there are countless companies that offer internet services by traditional means, there are also other companies that offer satellite internet service oriented to rural areas but their satellites are thousands of kilometers above the earth which makes your connection time is too high. Many times the connection to the internet by traditional means is not the most efficient in areas of difficult access, which is why two new satellite internet projects are currently being carried out with the use of satellites in low orbits. Starlink is the satellite internet project developed by the SpaceX company which seeks to launch about 12,000 satellites in low earth orbit, on the other hand, we have the Kuiper project, the same one that is developed by the Amazon company, this unlike SpaceX seeks to launch about 3,236 satellites into low orbit as well. Having satellites orbiting relatively close to the earth will result in faster connection response times, which translates to lower connection latency. Although both projects have differences in the number of satellites that will be launched, both Starlink and Kuiper have a common goal which is that they seek to compete with other internet providers (ISP) that provide their service through traditional transmission such as the radio link and fiber optics, providing an Internet service with global broadband coverage and low latency through the use of satellites.